Inventarisasi Spesies Tumbuhan Asing dan Potensi Pemanfaatannya di Areal Nilai Konservasi Tinggi Perkebunan Kelapa Sawit Provinsi Riau: Inventory of Alien Plant Species and Their Potential Utilization in High Conservation Value (HCV) Areas of Oil Palm Plantations in Riau Province - Nahlunnisa, Hafizah; Dwi Susanti, Amelia; Nurjannah, Siti (Jurnal Silva Tropika, 2026)
ABSTRACT The presence of alien plant species in High Conservation Value (HCV) areas of oil palm plantations has dual implications, posing potential threats to biodiversity while also providing ecological and economic benefits. This study aimed to inventory alien plant species occurring in HCV areas in Riau Province and identify their potential uses. The study was conducted through a reanalysis of primary vegetation inventory data collected from three HCV areas within oil palm plantations in Riau Province using a single-plot sampling method. Alien plant species were identified by referring to the Regulation of the Indonesian Ministry of Environment and Forestry No. P.94/2016, the Global Invasive Species Database, and A Guide Book to Invasive Plant Species in Indonesia. Information on their ecological functions and economic values was obtained through a literature review. The results identified 14 alien plant species belonging to nine families, with Asteraceae being the most dominant family (36%). Non-forest riparian HCV areas contained the highest proportion of alien plant species (34,4%), whereas no alien species were recorded in sialang forest patches. Ten species (76,9%) were found to provide important ecological functions, including ground cover, erosion control, soil fertility enhancement, forage for livestock and wildlife, and sources of botanical pesticides. All identified species also exhibited economic potential, particularly as medicinal plants, food resources, livestock forage, botanical pesticides, and timber resources. These findings suggest that the management of alien plant species in HCV areas should adopt a risk-based adaptive approach that considers the invasiveness, ecological functions, and economic value of each species.   Keywords: alien plants, biodiversity, high conservation value, invasive plants, oil palm plantations   ABSTRAK Keberadaan tumbuhan asing pada areal Nilai Konservasi Tinggi (NKT) perkebunan kelapa sawit memiliki implikasi ganda, yaitu berpotensi mengancam keanekaragaman hayati sekaligus memberikan manfaat ekologis dan ekonomi. Penelitian ini bertujuan menginventarisasi spesies tumbuhan asing pada kawasan NKT di Provinsi Riau serta mengidentifikasi potensi pemanfaatannya. Penelitian dilakukan melalui reanalisis data primer hasil inventarisasi vegetasi pada tiga areal NKT perkebunan kelapa sawit di Provinsi Riau yang dikumpulkan menggunakan metode petak tunggal. Identifikasi spesies asing dilakukan melalui pencocokan dengan Peraturan Menteri Lingkungan Hidup dan Kehutanan Nomor P.94 Tahun 2016, Global Invasive Species Database, dan A Guide Book to Invasive Plant Species in Indonesia, sedangkan informasi mengenai peran ekologis dan ekonomi diperoleh melalui kajian pustaka. Hasil penelitian mengidentifikasi 14 spesies tumbuhan asing dari sembilan famili, dengan famili Asteraceae sebagai kelompok terbanyak (36%). Areal NKT berupa sempadan sungai non-hutan memiliki proporsi tumbuhan asing tertinggi (34,4%), sedangkan kawasan hutan kepungan sialang tidak ditemukan spesies asing. Sebanyak 10 spesies (76,9%) memiliki peran ekologis sebagai penutup tanah, pengendali erosi, penyubur tanah, sumber pakan ternak dan satwa liar, serta biopestisida nabati. Seluruh spesies yang teridentifikasi juga memiliki potensi pemanfaatan ekonomi, terutama sebagai tanaman obat, pangan, pakan ternak, pestisida nabati, dan bahan baku kayu. Hasil penelitian menunjukkan bahwa pengelolaan tumbuhan asing di kawasan NKT perlu menerapkan pendekatan adaptif berbasis risiko dengan mempertimbangkan tingkat invasivitas, fungsi ekologis, dan nilai ekonomi masing-masing spesies.   Kata kunci: keanekaragaman hayati, nilai konservasi tinggi, perkebunan kelapa sawit, tumbuhan asing, tumbuhan invasif